1993
DOI: 10.1159/000126412
|View full text |Cite
|
Sign up to set email alerts
|

Intrahypothalamic Perfusion with lnterleukin-1-Beta Stimulates the Local Release of Corticotropin-Releasing Hormone and Arginine Vasopressin and the Plasma Adrenocorticotropin in Freely Moving Rats: A Comparative Perfusion of the Paraventricular Nucleus and the Median Eminence

Abstract: It is almost generally accepted that an acute-phase ACTH response induced by interleukin (IL)-1 is mediated principally by CRH release from the hypothalamus. However, the precise cellular site of action of IL-1 in activating the CRH neuronal system remains to be determined. Two likely candidates comprise the paraventricular nucleus (PVN) where CRH neuronal cell bodies are located, and the median eminence (ME) where their nerve endings are terminated. Therefore, in this study we performed a comparative perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 41 publications
3
47
0
Order By: Relevance
“…Temporal changes in plasma ACTH and CRH levels in the PVN were also monitored. To accomplish this, we employed the push-pull perfusion (PPP) technique of the rat brain as in our previous reports [24][25][26][27][28][29]. Second, we compared the effects of iv versus ip injections of LPS to determine if the route of administration causes any fundamental differences in response of the three cytokines in either the peripheral circulation or the PVN.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Temporal changes in plasma ACTH and CRH levels in the PVN were also monitored. To accomplish this, we employed the push-pull perfusion (PPP) technique of the rat brain as in our previous reports [24][25][26][27][28][29]. Second, we compared the effects of iv versus ip injections of LPS to determine if the route of administration causes any fundamental differences in response of the three cytokines in either the peripheral circulation or the PVN.…”
mentioning
confidence: 99%
“…Second, we compared the effects of iv versus ip injections of LPS to determine if the route of administration causes any fundamental differences in response of the three cytokines in either the peripheral circulation or the PVN. We chose the PVN as the site to determine cytokine levels, because that nucleus is where the CRH neuronal cell bodies are located, and we [27] and other investigators [30,31] have previously reported that the PVN may be a potential site within the hypothalamus where brainderived IL-1 activates the HPA axis. Adult male rats (350-400 g) of the WistarImamichi strain were used.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The minimally effective dose of IL-/I for AVP release into the VSA was between 125 and 500 pg (2 /sl)-' (approximately 10 nM). This is similar to that necessary to evoke AVP release from the median eminence in vivo (Watanobe & Takebe, 1993) but at least 100-fold less than that required to induce hypothalamic release of serotonin metabolites in vivo (Mohankumar, Thyagarajan & Quadri, 1993).…”
Section: Discussionmentioning
confidence: 66%